Removal of Basic Textile Dyes from Aqueous Solutions through Adsorption by Barks - Olcayto Keskinkan; Cagatayhan B. Ersu (Adsorption Science & Technology)
In this study, the adsorption capacities of Eucalyptus camaldulensis barks were investigated as an alternative tertiary treatment for the removal of textile dyes [Basic Blue (BB41) and Basic Yellow (BY51)] commonly used in the textile industry. The first set of experiments employed an initial dye concentration of 100 mg/ℓ and 3 g of tree barks in order to determine the contact time for breakthrough. Then, the adsorption isotherm constants were obtained for BB41 and BY51 employing concentrations varying between 25 mg/ℓ to 800 mg/ℓ and between 25 mg/ℓ to 500 mg/ℓ, respectively, using the same amount of E. camaldulensis barks. The constants determined via the Langmuir and Freundlich isotherms indicated that both isotherm models were adequate for explaining the adsorption process. According to the Langmuir isotherm, the maximum adsorption capacities (Q max ) of the E. camaldulensis barks for BB41 and BY51 were 164.17 mg/g and 54.68 mg/g, respectively. The applicability of various kinetic models was also investigated. The results indicated that the adsorption kinetics conformed to intra-particle diffusion. Finally, the dimensionless constant separation factor for the adsorbent/adsorbate system was determined.